2007
DOI: 10.1017/s0007114507750857
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor α is required for biochanin A-induced apolipoprotein A-1 mRNA expression in HepG2 cells

Abstract: Epidemiological studies have indicated that soya consumption may produce a better plasma lipid profile. The effect may be attributed to the phyto-oestrogens in soya. The red clover (Trifolium pratense) isoflavone biochanin A has a chemical structure similar to those phyto-oestrogens found in soya beans, and is marketed as a nutraceutical for alleviating postmenopausal symptoms. In the present study we investigated the effect of biochanin A on the mRNA expression of ApoA-1 in the hepatic cell line HepG2. Real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In fact, genistein has been previously demonstrated to be stronger than daidzein in increasing the gene expression of apolipoprotein A-I, a major component of high density lipoprotein, in HepG2 cells [ 20 ]. As the gene expression of apolipoprotein A-I is under the control of estrogen receptor-alpha [ 21 ], this effect is ascribable to the difference between these isoflavones in affinity for this receptor. Also, it has been reported that genistein interferes with the activation of CCAAT/enhancer-binding protein (C/EBP)β by inhibiting tyrosine-phosphorylation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, genistein has been previously demonstrated to be stronger than daidzein in increasing the gene expression of apolipoprotein A-I, a major component of high density lipoprotein, in HepG2 cells [ 20 ]. As the gene expression of apolipoprotein A-I is under the control of estrogen receptor-alpha [ 21 ], this effect is ascribable to the difference between these isoflavones in affinity for this receptor. Also, it has been reported that genistein interferes with the activation of CCAAT/enhancer-binding protein (C/EBP)β by inhibiting tyrosine-phosphorylation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%